2006
DOI: 10.1002/clc.4960290806
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a new index for estimating arterial stiffness: Measurement of the QPV interval by doppler ultrasound

Abstract: SummaryBackground: Pulse wave velocity (PWV), a relevant indicator of arterial stiffness, can be measured noninvasively with a variety of automatic devices, but most are complexly equipped. We developed a novel index for estimating arterial stiffness as "QPV interval," which was determined by means of surface electrocardiogram and Doppler ultrasound of the brachial artery simultaneously.Hypothesis: This study aimed to validate the QPV interval as an exact and convenient index for estimation of arterial stiffne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 19 publications
3
7
0
Order By: Relevance
“…The lack of an association of the QPV interval with height and heart rate was also noted previously. 9 In the present study, the QPV interval was similar in patients taking and not taking steroids, analogous to prior studies that demonstrated steroid use to have no effect on arterial stiffness. 2 The QPV interval represents the transit time from cardiac ejection to brachial artery flow.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…The lack of an association of the QPV interval with height and heart rate was also noted previously. 9 In the present study, the QPV interval was similar in patients taking and not taking steroids, analogous to prior studies that demonstrated steroid use to have no effect on arterial stiffness. 2 The QPV interval represents the transit time from cardiac ejection to brachial artery flow.…”
Section: Discussionsupporting
confidence: 87%
“…These results are similar to those of Lee et al, who compared the brachial-to-ankle PWV using volume plethysmography to the QPV interval in hypertensive and nonhypertensive normal subjects. 9 Mean QPV values were similar to the QPV values reported in that study. The lack of an association of the QPV interval with height and heart rate was also noted previously.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations